1984
DOI: 10.1002/cyto.990050511
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric analysis of megakaryocyte differentiation

Abstract: Megakaryocytes were isolated quantitatively from rat bone marrow by centrifugal elutriation (CE). CE-enriched megakaryocytes were stained supravitally for either (1) DNA content with Hoechst 33342, (2) surface membrane immunofluorescence with fluorescein isothiocyanate (FITC)-conjugated antiplatelet antibody, or (3) both. The cells were then measured using a Becton Dickinson FACS IV flow cytometer. The following correlations were analyzed: (1) DNA content and light scatter, (2) light scatter and antiplatelet i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…There was a marked dissociation between alterations in platelets and MK, since a statistically significant increase in platelet sectional area occurred 40 hr before the shift in modal ploidy class of MK, and platelet size subsequently decreased toward normal during the period that has been shown to be associated with the maximum shift in MK ploidy. These results strongly suggest that the characteristics of platelet release do not depend on the ploidy or cytoplasmic characteristics of MK.The process of thrombopoiesis remains controversial, particularly with respect to the normal megakaryocyte ploidy distribution (Bessman, 1984;Corash et al, 1987;Jackson et al, 1984;Levine et al, 1980;Worthington et al, 1984) and the determinants of platelet volume (Corash, 1985; Martin and Trowbridge, 1985). Recently, Corash et al (1987) used a murine model in which experimental immune thrombocytopenia was induced to evaluate the relationships between rnegakaryocyte ploidy and mean platelet volume.…”
mentioning
confidence: 88%
“…There was a marked dissociation between alterations in platelets and MK, since a statistically significant increase in platelet sectional area occurred 40 hr before the shift in modal ploidy class of MK, and platelet size subsequently decreased toward normal during the period that has been shown to be associated with the maximum shift in MK ploidy. These results strongly suggest that the characteristics of platelet release do not depend on the ploidy or cytoplasmic characteristics of MK.The process of thrombopoiesis remains controversial, particularly with respect to the normal megakaryocyte ploidy distribution (Bessman, 1984;Corash et al, 1987;Jackson et al, 1984;Levine et al, 1980;Worthington et al, 1984) and the determinants of platelet volume (Corash, 1985; Martin and Trowbridge, 1985). Recently, Corash et al (1987) used a murine model in which experimental immune thrombocytopenia was induced to evaluate the relationships between rnegakaryocyte ploidy and mean platelet volume.…”
mentioning
confidence: 88%
“…Studies in experimental mammals showed similar ploidy distribution. [16][17][18][19] It is of interest that, whereas immunofluorescence, size, and granularity increase continuously with cell maturation, ploidy increases in discrete steps (Figure 2). Thus, MK ploidy level may be useful for discrimination between cell maturation subsets.…”
Section: Discussionmentioning
confidence: 99%
“…Following initial studies in experimental animals, [16][17][18][19] the flow cytometric method was adapted for the analysis of human MKs derived from routine marrow aspirates, 9-11 thus permitting sequential studies of MKs in normal and pathologic states. Moreover, with the use of fluorescence-activated cell sorting of bone marrow aspirates, it becomes possible to isolate highly pure (Ն 98%) viable human MKs capable of synthesis of both DNA and protein in vitro and responsive to hematopoietic growth factors.…”
Section: Introductionmentioning
confidence: 99%
“…The DNA content of megakaryocytes has been commonly determined by a microphotometric method using Feulgen staining (Garcia 1964;Queisser et al 1971Queisser et al , 1972Queisser et al , 1974Nomura et al 1983), a microfluorometric method using DAPI staining (Kobayashi et al 1991) or flow cytometry using propidium iodide staining (Nakeff et al 1979;Worthington et al 1984;Tomer et al 1988). Each method has advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 99%